Peningkatan Jiwa Kewirausahaan Dan Daya Saing UMKM Pada Kelompok Usaha Satya Rahayu - I Gede Bayu Wijaya; I Gede Wira Suarantika; I Made Weda Semaradana; Ni Wayan Putriani; Ayu Diastini; Ni Nyoman Suli Asmara Yanti (IAHN Gde Pudja Mataram, 2023)
Commnity service is a self-empowerment process carried out to provide useful services to the local community. The impact of this pandemic is very big on almost all professions and worker in the creative economy, many employees are laid off, Micro business actors, many community business groups are closed. Fostering an entrepreneurial spirit is important with the aim that all business activities run well and reduce the risk of the failure of the business. The problem of lack of knowledge related to e-commerce, financial management to low motivation in entrepreneurship which result in low competitiveness, form the problems the service team arranges various activity program that are expected to solve these problems and solution that can be given to service participants. The data analysis technique in this service is a descriptive method by collecting data based on or in the form of words and pictures.